مكافحة الفساد والعقبات التي تواجهها: الأردن أنموذجاً - الجدوع، عاصم علي سليمان (الجامعة الأردنية - عمادة البحث العلمي, 2018)
This research presents a realistic and Practical studying for anti-corruption in Jordan, which it achieving through many ways whatever an executive legislative and judicial powers, as well as the controlling of public opinion and civil community. Despite the existence of this system but the results are disappointing and illogical. The first part of this study shows the mechanics and ways of controlling and struggling, while the second part of this study shows the reasons which weak the results of anti-corruption which refers to legislative reasons and others connected with the systems that pointed of anti-corruption. As well as there are cooperated groups work as a keeping 011 its Gains, an un awareness and a weakling of civil community organizations come through these reasons. The study concluded to putting the total of recommendations to treat a weakness points importantly modifying the legislations which ensuring independence the systems of controlling and its effectiveness.
يقدم هذا البحث دراسة واقعية وعملية لمكافحة الفساد في الأردن والتي تتم من خلال عدة وسائل وأساليب سواء من خلال السلطات الثلاث التنفيذية والتشريعية والقضائية، ورقابه الرأي العام والمجتمع المدني، وبالرغم من وجود هذه المنظومة في الأردن إلا أن النتائج مخيبة وغير ملموسة، حيث يعرض الجزء الأول من هذه الدراسة آليات ووسائل النيابة والمكافحة، في حين يناقش الجزء الثاني من الدراسة الأسباب التي تضعف نتائج مكافحة الفساد، والتي ترجع إلى أسباب تشريعية، وأخرى مرتبطة بذات الأجهزة المكلفة بمكافحة الفساد، وكذلك وجود مجموعات متضامنة تعمل حفاظا على مكتسباتها، ويأتي انعدام الوعي وضعف منظمات المجتمع المدني ضمن هذه الأسباب حيث خلصت الدراسة إلى وضع مجموع من التوصيات لمعالجة مكامن الخلل وأهمها تعديل التشريعات بما يضمن استقلال أجهزة الرقابة وفعاليتها.
Keywords: الفساد -- مكافحة الفساد -- الأردن